2014
DOI: 10.3945/ajcn.113.081521
|View full text |Cite
|
Sign up to set email alerts
|

Dietary sugars and cardiometabolic risk: systematic review and meta-analyses of randomized controlled trials of the effects on blood pressure and lipids

Abstract: Dietary sugars influence blood pressure and serum lipids. The relation is independent of effects of sugars on body weight. Protocols for this review were registered separately for effects of sugars on blood pressure and lipids in the PROSPERO International prospective register of systematic reviews as PROSPERO 2012: CRD42012002379 and 2012: CRD42012002437, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
299
1
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 437 publications
(333 citation statements)
references
References 72 publications
9
299
1
10
Order By: Relevance
“…Even the Food and Drug Administration's proposed changes to packaged-food labels -which would newly report the amount of 'added sugars' in a product -place even more emphasis on calories than current labels by visually subordinating all other label information and highlighting calories in an enormous bold typeface (128) . What existing and planned initiatives seem not to acknowledge is that calories from added sugars and starches are worse than just 'empty' (detriment through omission); evidence suggests they are actively harmful (detriment through commission) (61,62,129,130) . While responses of individual consumers may vary (e.g.…”
Section: More-nuanced Thinking About Obesity and Related Diseasesmentioning
confidence: 99%
“…Even the Food and Drug Administration's proposed changes to packaged-food labels -which would newly report the amount of 'added sugars' in a product -place even more emphasis on calories than current labels by visually subordinating all other label information and highlighting calories in an enormous bold typeface (128) . What existing and planned initiatives seem not to acknowledge is that calories from added sugars and starches are worse than just 'empty' (detriment through omission); evidence suggests they are actively harmful (detriment through commission) (61,62,129,130) . While responses of individual consumers may vary (e.g.…”
Section: More-nuanced Thinking About Obesity and Related Diseasesmentioning
confidence: 99%
“…[75][76][77] High sugar intake has also been associated with higher blood pressure (mean difference 6.9 mmHg [95% confidence interval (CI): 3.4, 10.3 mmHg; P,0.001 compared with low sugar intake] for systolic blood pressure and 5.6 mmHg [95% CI: 2.5, 8.8 mmHg; P=0.0005] for diastolic blood pressure). 78 The other notable effect of a high sugar intake is on triglycerides (mean difference: 0.11 mmol/L; 95% CI: 0.07, 0.15 mmol/L; 78 There is also evidence that sugar intake directly influences development of T2DM. In women consuming one or more sugar-sweetened beverages per day, the diabetes relative risk was 1.83 when compared with those who had one drink per month.…”
Section: Dietary Sugarmentioning
confidence: 99%
“…They have showed that sugar has a potential of causing fluid and sodium overload [5]. According to a meta-analysis of Randomised Control Trials (RCT), it was observed that that a diet with high sugar quantity as compared with a low-sugar diet, could cause an increase in blood pressure [6] Moreover, sugar can lead to leptin resistance, which may also contribute to its BP raising effects [7]. Dietary sugar may also increase aldosterone by activation of the sympathetic nervous system, which stimulates angiotensin-II and aldosterone production from adrenal glands [8].…”
Section: Association Of Sugar and Hypertensionmentioning
confidence: 99%